2006
DOI: 10.1590/s1135-57272006000300003
|View full text |Cite
|
Sign up to set email alerts
|

Factores asociados al control de la hipertensión arterial en personas mayores de 60 años en España

Abstract: RESUMENFundamento: En la última década se ha observado una mejora en el control de la hipertensión arterial en España. Dicho control repercute en la disminución de la morbimortalidad cardiovascular. El objetivo de este trabajo es identificar los factores asociados al control de la hipertensión arterial en varones y mujeres hipertensos diagnosticados que reciben tratamiento farmacológico. Métodos:Estudio descriptivo transversal, realizado a partir de los datos del estudio: «Hipertensión arterial y otros factore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(42 reference statements)
0
1
0
1
Order By: Relevance
“…The authors reported that one up to four subjects had a diagnosis of hypertension, in accordance with our study results, and as in the previously mentioned ENRICA study [ 26 ], only 1 of 2 subjects was aware of its hypertensive status. Another population-based study in subjects aged ≥ 60 years old found that BP control was related to living in rural areas, as we have found in rural women, being uncoupled or doing moderate physical activity in men, as well as drinking moderate alcohol in women [ 11 ]. Relevant of this study is that it is one of the few studies in Spain that clearly defines and addresses the living area, a factor that in our opinion should be considered in the study of hypertension prevalence and incidence, as a consequence of the different ways of live [ 10 12 , 16 ].…”
Section: Discussionmentioning
confidence: 62%
“…The authors reported that one up to four subjects had a diagnosis of hypertension, in accordance with our study results, and as in the previously mentioned ENRICA study [ 26 ], only 1 of 2 subjects was aware of its hypertensive status. Another population-based study in subjects aged ≥ 60 years old found that BP control was related to living in rural areas, as we have found in rural women, being uncoupled or doing moderate physical activity in men, as well as drinking moderate alcohol in women [ 11 ]. Relevant of this study is that it is one of the few studies in Spain that clearly defines and addresses the living area, a factor that in our opinion should be considered in the study of hypertension prevalence and incidence, as a consequence of the different ways of live [ 10 12 , 16 ].…”
Section: Discussionmentioning
confidence: 62%
“…Representando un problema creciente de salud pública, debido a que la expectativa de vida se incrementa en países desarrollados y la tendencia es similar en países en desarrollo, constituyendo el grupo poblacional con el mayor crecimiento (28) (29).…”
Section: Hipertensión Sistólica Aislada (Hsa)unclassified